Consumo autorreferido de plantas medicinais por idosos - Rodrigues, Bianca Pereira (2017)
The elderly constitute the portion of the population that often uses home remedies prepared with medicinal plants and, besides users, are holders and disseminators of popular / traditional knowledge of great utility to the community. Therefore, this study aimed to evaluate the self-referenced use of medicinal plants (PM) from the perspective of the knowledge, beliefs and practices of the elderly enrolled in the Family Health Strategy at the Family Health Unit Edvaldo Silva, Maceió-AL. This is a descriptive, quantitative cross-sectional epidemiological study. The investigation was carried out in the neighborhood of Fernão Velho, Maceió-AL and the data collection was done through interviews in the homes of the elderly in the period from January to September 2016. The database was built and analyzed in the program EpiInfo version 7.1.3 , as well as the data analysis was processed using the Statistical Package for Social Sciences (SPSS) for Windows, version 13.0. The collection of medicinal plants was carried out only in the homes of the elderly who authorized the collection of samples for botanical identification (period from December 2016 to March 2017). The identification of the viable samples was made by the botanist Rosângela Pereira of Lyra Lemos and deposited in the MAC Herbarium of the Institute of the Environment. This work was approved by CEP / UFAL under number 50092615.6.0000.5013. Data analysis showed that the sample of the elderly was composed of 103 subjects with a predominance of female gender (75.7%) and age group of 60-69 years (41.8%); 40.8% of the subjects were married and 62% reported incomplete primary education as their level of education; 80.6% of the elderly have as income only a minimum wage; and 95% live in their own homes. Of the elderly people interviewed, 96% reported having some morbidity, with the most prevalent circulatory diseases (83.5%), such as hypertension and endocrine and metabolic diseases (39.8%), such as diabetes mellitus. Regarding the knowledge and practices of PM, we found that 98% of the elderly believe that PM can cure and 49.5% attributed harmlessness to these products; 91.3% self-reported the use of this therapy and 90.3% reported that they prepare home remedies with PM. The knowledge source of the elderly in relation to the preparation of home remedies of PM was mostly attributed to their relatives (59%). In addition, 92.2% of the elderly reported that they would like the prescribing of PM / Phytotherapics by the doctors and 91% said that it would be interesting to distribute herbal medicines in the Unified Health System. We identified 191 references of PM plants by the elderly, the main indications reported were diseases of the digestive system; symptoms and signs (pain, fever, cough, among others); and mental and behavioral disorders. Of the species collected, the botanical identification of five plants was carried out, which were: Lippia alba (Mill.); Borreria verticillata (L.); Phyllanthus niruri L .; Turnera subulata Sm (MAC Reg. 63732); and Solanum paniculatum L. (MAC Reg. 63733), when comparing the use of these plants cited by the elderly with the literature we observed that the elderly use the correct part of the plant and the clinical indications cited corroborate with those described in the literature. Therefore, the results of this work show us that the elderly of the community of Fernão Velho possess a rich ethnopharmacological knowledge regarding the medicinal plants and make use of this therapy. However, despite the work being carried out in a single neighborhood of Maceió, the information identified indicates that the popular use of medicinal plants is still present in our city, as well as other studies showing the reality of the city of Maceió in relation to the use of medicinal plants / phytotherapy, thus helping in the development of programs and public policies for the implementation of phytotherapy in our city.